2019
DOI: 10.1021/acs.jmedchem.8b01325
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of a New Series of Carvedilol Derivatives That Protect Sensory Hair Cells from Aminoglycoside-Induced Damage by Blocking the Mechanoelectrical Transducer Channel

Abstract: Aminoglycosides (AGs) are broad-spectrum antibiotics used for the treatment of serious bacterial infections but have use-limiting side effects including irreversible hearing loss. Here, we assessed the otoprotective profile of carvedilol in mouse cochlear cultures and in vivo zebrafish assays and investigated its mechanism of protection which, we found, may be mediated by a block of the hair cell's mechanoelectrical transducer (MET) channel, the major entry route for the AGs. To understand the full otoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…This would allow for temporary charges to reside within the structure which may form favorable electrostatic interactions with its target and could explain why quaternary versions of protective drugs such as ORC-13661 are more active. This is further supported by evidence from Chowdhury et al ( 2018 ) and O’Reilly et al ( 2019 ). Both studies found that aminoglycoside otoprotection required a basic center with a positive charge to engage in electrostatic interactions, such as basic nitrogen or a quaternary ammonium salt.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…This would allow for temporary charges to reside within the structure which may form favorable electrostatic interactions with its target and could explain why quaternary versions of protective drugs such as ORC-13661 are more active. This is further supported by evidence from Chowdhury et al ( 2018 ) and O’Reilly et al ( 2019 ). Both studies found that aminoglycoside otoprotection required a basic center with a positive charge to engage in electrostatic interactions, such as basic nitrogen or a quaternary ammonium salt.…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, aryl groups are present in other protective compounds such as tacrine, berbamine, carvedilol, ORC-13661, and phenoxybenzamine, suggesting the importance of the aryl moiety for otoprotection (Ou et al, 2012 ; Kruger et al, 2016 ; Chowdhury et al, 2018 ; O’Reilly et al, 2019 ). It is likely that the phenyl group, among other aryl groups, may be necessary for protection due to their unusual stability and ability to delocalize charges within their structure by resonance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar channel interaction has been reported for the alkaloid d-tubocurarine (29). These results demonstrate that ORC-13661 is, similar to the AGs themselves and other positively charged compounds, a permeant blocker of the MET channel (12, 29, 55).…”
Section: Resultsmentioning
confidence: 62%